2018
DOI: 10.1002/ptr.6225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic supplementation on serum C‐reactive protein level: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The present study was designed to systematically review randomized controlled trials (RCTs) that report on the effects of garlic supplementation on serum C-reactive protein (CRP) levels. We conducted a literature search of Scopus, PubMed, Cochrane Library, and Google Scholar up to January 2018. Weighted mean differences (WMD) were estimated for net change in serum CRP. Subgroup analyses were also performed by duration of study, dose of supplementation, baseline CRP level, and the quality of studies. From 438 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Therefore, the current trial showed that the garlic treatment can contribute to reducing the risk of CVDs in patients with NAFLD independent of potential risk factors. Our findings are consistent with a recent meta‐analysis study in which the administration of garlic significantly decreased serum concentrations of hs‐CRP by 0.82 mg/Dl (Taghizadeh et al., 2019). These findings are worth noting because cardiovascular events are the leading cause of premature death in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the current trial showed that the garlic treatment can contribute to reducing the risk of CVDs in patients with NAFLD independent of potential risk factors. Our findings are consistent with a recent meta‐analysis study in which the administration of garlic significantly decreased serum concentrations of hs‐CRP by 0.82 mg/Dl (Taghizadeh et al., 2019). These findings are worth noting because cardiovascular events are the leading cause of premature death in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 93%
“…Among the 31 studies, 11 studies (Chiavarini et al, ; Fleischauer et al, ; Guercio et al, ; Hu et al, ; Kodali & Eslick, ; Li et al, ; Turati et al, , ; Zhou et al, , ; Zhu et al, ) were about cancer and tumor outcomes (gastric cancer, colorectal cancer, upper aerodigestive tract cancer, prostate cancer, and colorectal adenomatous polyps), 13 studies (Emami et al, ; Khoo & Aziz, ; Kwak et al, ; Reinhart et al, ; Ried, ; Ried, Toben, et al, ; Sahebkar et al, ; Shabani et al, ; Stevinson et al, ; Sun et al, ; Wang et al, ; Warshafsky et al, ; Zeng et al, ) were about metabolic outcomes (serum total cholesterol [TC], high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], triglycerides [TGs], fasting blood glucose [FBG], serum HbA1c, serum fructosamine, serum lipoprotein (a), and apolipoprotein B), seven studies (Reinhart et al, ; Ried, ; Ried et al, ; Rohner et al, ; Silagy & Neil, ; Wang et al, ; Xiong et al, ) were about cardiovascular outcomes (systolic blood pressure and diastolic blood pressure), and only one systematic review and meta‐analysis (Taghizadeh et al, ) was about serum C‐reactive protein levels. Finally, 50 unique outcomes extracted from the 16 most recent meta‐analyses were analyzed in this umbrella review, and the map of allium vegetable‐related outcomes is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…There was only one inflammatory outcome, C‐reactive protein, reported in a meta‐analysis of nine intervention studies (Taghizadeh et al, ). The results of the random effects model showed that garlic significantly reduced the level of C‐reactive protein (WMD −0.80 mg/L; 95% CI −1.50 to −0.10) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to anti-atherogenic effects, garlic has shown to have anti-inflammatory and antioxidant effects. A recent meta-analysis including nine RCTs (Allium supplement: ≥1200 mg/day or <1200 mg/day) reported significant reductions in the CRP levels (weighted mean difference (WMD): −0.8 mg/L, 95% confidence interval (CI): −1.5, −0.1, p = 0.02) [84]. Similar results (12 to 3600 mg/day of AGE, 16 RCTs) were described by Darooghegi et al [85], who reported significant changes in CRP concentrations (WMD: −0.61 mg/L, 95% CI: −1.12, −0.11, p = 0.018).…”
Section: Health Potential Of Selected Fruits and Vegetablesmentioning
confidence: 99%